Idealization of planting density and nitrogen levels for density tolerant baby corn - Shanti Devi Bamboriya; Pradeep Kumar (Annals of Agricultural Research, 2023)
Baby corn (Zea mays L.) is a short duration crop that generate large amount of profit in comparatively lesser time span. The high density tolerant cultivars have different optimum plant population as well as nitrogen requirement. Therefore, a field study was planned to find out best density and nitrogen level for density tolerant baby corn. The experiment was laid out in split plot design with three replications. The treatments comprised of four density levels (111111; 148000; 222222 and 296296) and three doses of nitrogen (150, 180 and 210 kg N/ha). High density planting (296296 plants/ha) produced taller plants with more cobs per ha that resulted into higher green fodder yield (40.0 t/ha) and cob yield (3.1 t/ha), respectively. Additional application of nitrogen beyond 150 kg/ha increased plant height, cob number per plant, cob weight and corn/cob ratio. Moreover cob and fodder yields were also increased with increase in nitrogen levels. Planting of 296 296 plants per ha with the application of 210 kg N/ha was observed the best treatment combination as compared to rest other combinations in terms of cob yield.